Modular anthropomorphic grippers – structural synthesis, analysis and design - Staretu, Ionel A. (Vojnotehnički glasnik / Military Technical Courier, 2014)
In general, anthropomorphic grippers for robots are similar to the human hand and they can have two, three, four or more fingers, with two or three phalanxes. Anthropomorphic grippers for robots compared to other mechanical grippers have more advantages such as: a higher degree of dexterity, a larger area of utility (more types of objects can be grasped) and a micro-movement of the grasped objects can be performed. This paper describes two groups of anthropomorphic grippers for robots: traditional mechanical anthropomorphic grippers and modular mechanical anthropomorphic grippers designed under the author’s coordination. For the first group, more versions with two, three, four and five fingers are shown and for the second group, there are more modular solutions shown. The stages of synthesis, analysis, design, and functional simulation are briefly shown as well.